PRAKTIK SEWA MENYEWA PERALATAN KEMAH DALAM BINGKAI HUKUM EKONOMI SYARIAH - Latifa, Latifa; Nadia, Nadia (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
Exploring the rental practices of camping equipment within the framework of Sharia economic law is an area that has not been extensively researched. This study aims to describe the rental practices of camping equipment at the Handy Talky and Tent Rental Outlet in Palu and to assess their compliance with the principles of Sharia business contracts. The research methodology employed is empirical, utilizing interviews and direct observation as the primary data collection techniques. This approach seeks to understand the application of law in real social interactions. The study reveals that the rental process of camping equipment at the Handy Talky and Tent Rental Outlet in Palu involves several stages, from equipment selection to the return of the items. This practice reflects the application of Sharia business contract principles such as al-Hurriyah (freedom to contract), al-Musawah (equality), al-‘Adalah (justice), al-Ridhaiyyah (mutual consent), Ash-shidiq (honesty), and al-Kitabah (written documentation). Although these principles are generally adhered to, there is a weakness in the detailed written documentation. Conversations on social media and borrower records do not cover all the essential aspects of the agreements. The study suggests that to enhance compliance with Sharia business contract principles, more comprehensive and formal written contracts are needed. This research provides valuable insights for the development of policies and business practices that are more aligned with Sharia economic law.